A meta‐analysis on the diagnostic performance of magnetic resonance imaging and transient elastography in nonalcoholic fatty liver disease. (9th December 2020) - Gu, Qing; Cen, Li; Lai, Jiawei; Zhang, Zhongchen; Pan, Jiaqi; Zhao, Feng; Yu, Chaohui; Li, Youming; Chen, Chunxiao; Chen, Weixing; Shen, Zhe
Abstract: Background: Noninvasive methods have been used for the assessment of hepatic steatosis in patients with nonalcoholic fatty liver disease (NAFLD). The aim was to assess the efficacy and accuracy of both magnetic resonance imaging(MRI) and transient elastography(TE) for the evaluation of hepatic steatosis. Materials and Methods: The PubMed, Cochrane Library, Embase, MEDLINE and Web of Science databases were searched to retrieve studies examining the accuracy of MRI‐proton density fat fraction(PDFF) and TE‐controlled attenuation parameter(CAP) for evaluating the grading of steatosis(S0‐S3) diagnosed by liver biopsy in NAFLD. We compared the sensitivity, specificity, hierarchical summary receiver operating characteristic curves(HSROC) and clinical utility of these methods. Results: Twenty‐four articles with a total of 2979 patients with NAFLD were included. The steatosis distribution was 8.1%/35.1%/32.2%/24.6% for S0/S1/S2/S3. For the diagnostic accuracy of MRI‐PDFF, the HSROCs were 0.97 for ≥S1, 0.91 for ≥S2 and 0.90 for ≥S3. For the diagnostic accuracy of TE‐based CAP, the HSROCs were 0.85 for ≥S1, 0.83 for ≥S2 and 0.79 for ≥S3. Following a 'positive' measurement (over the threshold value) for ≥S1, the corresponding post‐test probabilities of PDFF and CAP for the presence of steatosis were 82% and 61%, respectively, when the pretest probability was 24%. If the values were below these thresholds ('negative' results), the post‐test probabilities were 3% and 7%. Conclusion: MRI‐PDFF and TE‐CAP both provide highly accurate noninvasive approaches for quantifying and staging hepatic steatosis in NAFLD. Compared with TE‐CAP, MRI‐PDFF is significantly more accurate for evaluating dichotomized grades of steatosis.